A portable abstraction layer for hardware threads - Lubbers, E.; Platzner, M. (2008 International Conference on Field Programmable Logic and Applications, 2008)
The multithreaded programming model has been shown to provide a suitable abstraction for reconfigurable computers. Previous implementations of corresponding runtime systems have been limited to a single host operating system, hardware platform, or application domain. This paper presents the implementation of ReconOS, our hardware/software multithreaded programming model, on both eCos and Linux-based host systems as well as on PowerPC and MicroBlaze CPUs. This demonstrates that ReconOS provides a truly portable abstraction layer for programming reconfigurable computers. Further, we quantify the performance of operating system calls and measure the resulting application level performance.